Death rattle : [large type] The guns of Samuel Pritchard - Lynch, Sean, active 2013- (Lynch, Sean Guns of Samuel Pritchard, 2020)
In 1863, a teenaged boy fled his home in Atherton, Missouri, to escape the power-hungry men who murdered his father and stole his family's land. He joined the Confederacy under an assumed name and led guerilla raids in the Civil War. Then came a decade as a Texas Ranger. Now, after ten blood-soaked years, he is finally coming home and finally using his real name and finally getting revenge against the cold-hearted devils who destroyed his family and his life.